FAKTOR PENYEBAB GURU STRES PADA CARA BELAJAR ANAK TUNAGRAHITA DI SLB KECAMATANSUNGAI AUR KABUPATEN PASAMAN BARAT - Miswanti, Miswanti; Hasan, Marwisni; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This research has background with there is students that have latest mentality, the teacher felt stress who has changed rare. The students seldom made strange behavior such as: fall asleep, saliva hatch, playing while studied. Â Problem in this research is effect factor teacher stress to the way studied tunagrahita students. Informan in this research is the teacher that teaching tunagrahita students in SLB have two peoples, research date collected through interview, observation and documentation. The result of this research exsplained that (1) effect factor teacher stress to the way tunagrahita students studied seen from fisiologis condition that come from teacher physic that teaching is healthy when teaching still less, in teaching the teacher less spirit saw condition the students that have less spirit in learning process, the teacher often lazy to study or did not spirit. (2) effect factor the teacher stress to the way studied tunagrahita students seen from fisiologis condition the teacher often felt nervous when teaching because the students often went out from class Â at the moment. Basen on this research recomended to the to the teacher that teaching in order be fatient in guide students who have latest in guide students who have latest mentality, in order the teacher better made relationship with.